HUBUNGAN KOMPOSISI TUBUH DAN TINGKAT AKTIVITAS FISIK DENGAN KEJADIAN NYERI MUSKULOSKELETAL PADA PEKERJA MINIMARKET - Hasbi, Alfian; Laeto, Arwan Bin; William, Jessica Audrey; Zulissetiana, Eka Febri; Santoso, Budi (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Musculoskeletal pain is acute or chronic pain, either persistent or recurring, that affects bones, muscles, ligaments, tendons, and nerves. According to Riset Kesehatan Dasar tahun 2018, the prevalence of musculoskeletal diseases in Indonesia has reached 7,3%. One of the risk factors is body composition and physical activity. This study aims to determine the relationship between body composition and physical activity with musculoskeletal pain among minimarket workers in Palembang City. An observational analytic study with a cross-sectional design was conducted on 50 respondents. Body composition was measured using Bioelectrical Impedance Analysis, while data on physical activity levels and musculoskeletal pain were collected using the International Physical Activity Questionnaire-Short Form and the Nordic Body Map Questionnaire. The study results show that the majority of minimarket workers had overfat body composition (32%); moderate physical activity levels (46%); and low risk of musculoskeletal pain (38%), with the most common areas of pain were the back and waist (40%). Bivariate analysis using Pearson’s Chi-Square test between body composition and musculoskeletal pain showed PR = 15.625 and p-value < 0.001. Meanwhile, the analysis of physical activity levels and musculoskeletal pain showed PR = 2.311 and p-value = 0.166. Thus, there is a significant relationship between body composition and musculoskeletal pain. However, there is an insignificant relationship between physical activity levels and musculoskeletal pain among minimarket workers in Palembang City.